Multicentric Reticulohistiocytosis Associated with Liver Carcinoma: Report of a Case - Ling Han; Qiong Huang; Kang-Huang Liao; Lian-Jun Chen; Wen-Yi Kong; Wen-Wen Fu; Jing-hua Xu (Karger Publishers, 2012)
We report a unique case of multicentric reticulohistiocytosis (MRH) associated with liver carcinoma. A 61-year-old man presented with a 4-month history of nonpruritic, generalized, ruby-red papules and nodules, accompanied by fever, joint swelling and difficulty in swallowing. Skin histology showed polymorphic histiocyte infiltration with typical 'ground glass' cytoplasm. Further immunohistochemical studies characterized the lesions as positive for leukocyte common antigen, HLA-DR and CD68. The patient had a history of hepatitis B, and systemic examination, including carcinoma index and type-B ultrasonic examination, revealed high levels of AFP and a solid tumor, which was considered malignant, localized on the right lobe of the liver. Treatment of the liver carcinoma resulted in a significant improvement of the skin symptoms. This is the first case study to report an association between MRH and liver carcinoma. A review of the English-language literature reveals the close linkage between MRH and malignancy. All patients with MRH should be evaluated and monitored carefully to determine the underlying neoplasm.